The Concept of Progressive Islam and the Pribumization of Islam in the Locality of Islam in Indonesia - Yasmin, Arini Dina; Umam, Fawaizul; Faizin, M. Khoirul (Islamika Inside: Jurnal Keislaman dan Humaniora, 2024)
Abstract: Indonesia, with its abundant cultural and religious wealth, faces challenges from radical Islamic groups that are incompatible with local values and pluralism. These groups which tend to hold exclusive and intolerant. The two main approaches that have emerged for interpreting Islam in this context are progressive Islam and Islamic indigenization. Progressive Islam, pioneered by Farish A. Noor encourages the adaptation of Islamic teachings to the values of modernity such as democracy, human rights, and pluralism. Meanwhile, the indigenization of Islam developed by Abdurrahman Wahid emphasizes the importance of integrating Islam with Indonesia's local culture. Both approaches reject radicalism and support an inclusive and tolerant form of Islam. However, they differ in focus and implementation, Farish is more global and theoretical, while Gus Dur is more local and practical. Both approaches are visible in social practices, Farish and Gus Dur support pluralism and human rights, although Gus Dur also emphasizes the importance of local cultural adaptation in daily religious practice. This research uses a descriptive qualitative method through a literature review of the works of Farish and Gus Dur, analyzing the main themes of each approach. The results show that despite their differences, these two approaches can complement each other in promoting relevant and contextualized Islam, contributing to social harmony and inclusive policies in Indonesia.